Shares with different nominal values based on the company law and capital market law - Ari Pratama Nawazzar; Angie Andiani; Chrysanthemum Sekar Seccio; KMS Fajri Pratama (The International Journal of Politics and Sociology Research, 2023)
The Indonesian monetary crisis has significantly affected the capital market and investment stability. To improve performance, Indonesian companies seek to raise capital but face the challenge of issuing shares at the same par value stated in their articles of association. This research lie in offering guidance to Indonesian companies on issuing new shares, ensuring equitable treatment of shareholders, and informing legal practitioners and policymakers about the implications of shares with different face values on corporate governance and investor protection. The formulation of the problem in this study is: which shares can be categorized as a classification of shares as stipulated in the Company Law? and How are voting rights and profit sharing in Company to shareholders who own shares with a different face value? This study uses a normative juridical method by collecting data from literature studies. Based on the results of the research, it is found that both listed and foreign companies need to issue new shares with different values than those specified in the articles of association. Despite the varying par values, these new shares grant shareholders equal rights, including voting rights, dividend distribution, and asset distribution in case of liquidation.